Theoretical and conceptual guide for investment and factors affecting investment in Baghdad Governorate - Al-Saadi, Wassan Khazal Abdul-Adheem; Abdul-lateef, Makki Ghazi (Al-Adab Journal, 2020)
The research included the concept of investment and investment projects, being the main part in building the investment map for the Baghdad Governorate, and clarifying the factors affecting it and clarifying the determinants and criteria of investment that affect the establishment of investment projects and the reasons behind this discrepancy. In particular, as a set of factors affecting the success of the investment process crystallize according to a set of criteria and determinants that are reflected in the reality surrounding the investment process, whether natural or human The security situation and political stability as the highlight of these factors.